PENERAPAN KONSEP GOOD GOVERNANCE DALAM PELAKSANAAN PEMBANGUNAN EKONOMI DI DESA TELUK KELASA KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR TAHUN 2018 - Zainal Abdullah; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Teluk Kelasa village is a village located in Keritang District of Indragiri Hilir Regency of Riau Province with a width of 4,000 Km and a length of 5,000 Km. The village of teluk kelasa is divided into 4 hamlets, Referring to the Vision and Mission of the Head of Teluk Kelasa Village and considering the evaluation and review of RKP and RPJM Desa the previous year through the village deliberation process then in general the Village Development Program is the same as the direction of village development policy, one of which is the Infrastructure Basic Service Program, infrastructure found in Kelasa Bay Village namely roads and bridges in 2018 is still in a concerned condition where the road that every day becomes the basic service needs of the community can not meet the needs or does not meet the expectations of the community.The purpose of this research is to find out the implementation of road and bridge construction in Teluk Kelasa village year 2108. This research uses a qualitative approach with descriptive methods. In data collection, authors use interview techniques, document searches and documentation. Village Development aims to improve the welfare of villagers and the quality of human life as well as poverty reduction through the fulfillment of basic needs, development of village facilities and infrastructure, development of local economic potential, and sustainable utilization of natural and environmental resources, Village Development includes the planning, implementation, and supervision stages.The result of this research is that the village of kelasa bay has carried out economic development activities using the village budget from the central and the allocation of provincial and district village funds, which is carried out by the village government and assisted by the partispasi of the villagers carrying out village development both in terms of roads and bridges, but from the result of the construction of roads and bridges in the village of kelasa bay has not been implemented to the maximum in 2018 due to several factors such as delays in the development of village funds and the allocation of village funds , difficulty access to heavy equipment for the construction of roads and bridges, poor weather conditions, and the certainty of less people.Keywords : Community Participation, Consensus Oriented, Effectiveness and Efficiency.